If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6x + -2) + -5(x + -3) = 0 Reorder the terms: 4(-2 + 6x) + -5(x + -3) = 0 (-2 * 4 + 6x * 4) + -5(x + -3) = 0 (-8 + 24x) + -5(x + -3) = 0 Reorder the terms: -8 + 24x + -5(-3 + x) = 0 -8 + 24x + (-3 * -5 + x * -5) = 0 -8 + 24x + (15 + -5x) = 0 Reorder the terms: -8 + 15 + 24x + -5x = 0 Combine like terms: -8 + 15 = 7 7 + 24x + -5x = 0 Combine like terms: 24x + -5x = 19x 7 + 19x = 0 Solving 7 + 19x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 19x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 19x = 0 + -7 19x = 0 + -7 Combine like terms: 0 + -7 = -7 19x = -7 Divide each side by '19'. x = -0.3684210526 Simplifying x = -0.3684210526
| L=2+w | | 56x=1.4 | | x(1-c^2+4c)=7c-28 | | X+80+51+60=180 | | 3x^2+4y^2-18x+8y+19=0 | | 5x+6=2x-8 | | 4x+2x=15+25 | | X+6a-9=30 | | 48=2+w*w | | 3.14(r^2*120)=37680 | | 6X-3X=5 | | -5N+22+7N=46 | | -10N+10+8N=18 | | (4-v)(2v-3)=0 | | -3X-2X=-1 | | (x+5y)(3x+4y)= | | 0.11y+0.03(y+8000)=660 | | 7y+3=6y-8 | | 7(4x+9)-10=-87 | | 12b-9+2b-b=48 | | 15x+9y=53 | | -97+32-(-11)= | | (x-7)(x^2-3x+6)= | | -16t^2+vt+49=0 | | -3=2(X+4)+X | | 4*2+3x-27=0 | | h(t)=2t^4-t^3+6t^2+2t-8 | | 3(x-8)=-6 | | 0=-16t^2+49 | | 4x=3.2whatisx | | X+8=5(3X-2) | | 10x+8=0 |